Second Administrative Reforms Commission on personnel administration - Need to implement recommendations - Mathur, B.P. (2010)
The Administrative Reforms Commission (ARC) has adopted a bold and progressive approach to reform public administration by laying emphasis on performance of duty and making public servants accountable for delivering results. It has come out with a wide range of suggestions regarding recruitment, training and capacity building of civil servants so that a professionally competent work-force could be built up. ARC calls for rigorous performance appraisal of employees, which should form the basis of their promotion and career advancement. Those found unfit should be weeded out. There is a need to give quick and summary punishment to defaulting public servants, for which a simplified disciplinary regime should be put in place. The ARC underlines the importance of specialised knowledge for appointment to senior posts in Central Secretariat, for which an element of competition should be introduced. Public servants should inculcate high ethical standards for which an Ethics Code should be prescribed. - Reproduced.
Keywords: Administrative reform; Personnel management